Impact of food insecurity and food environment on the diet quality of older African Americans during the COVID-19 pandemic - Kibe, Lucy W.; Schrode, Katrina; Bazargan, Mohsen; Shaheen, Magda (Frontiers in Public Health, 2023)
Introduction A high quality diet is vital in promoting wellbeing and ensuring good health, particularly for those living with chronic conditions. Older African Americans, already burdened with a higher prevalence of chronic conditions, also face a higher risk for suboptimal diets. The COVID-19 pandemic had lasting effects on access to healthy food for all Americans, but some demographic groups were disproportionately affected. Older African Americans, who already experienced reduced access to healthy food pre-pandemic, were particularly afflicted, but the full extent of the pandemic's impact on their food insecurity and food environment remains unclear. Methods To address this gap, we conducted a study among 102 older African Americans in South Los Angeles between October 2021 and July 2022 during the COVID-19 pandemic. Participants completed surveys on dietary intake, food insecurity, and neighborhood food environment. We measured dietary quality using the healthy eating index (HEI)-2015. The analysis included descriptive, bivariate chi-square, t-tests, analysis of variance, and multiple linear and logistic regression. Results While overall dietary quality was suboptimal, most participants met the guidelines for fruit and vegetable consumption. Food insecurity was associated with lower overall diet quality and lower total fruit and whole fruit intake. However, there was no association between food environment and diet quality. Discussion In light of our findings, further intervention is critical to improving diet quality, especially among older African Americans living with chronic conditions in the post-pandemic era.